Blood red road - Young, Moira (London : Marion Lloyd Books : Scholastic, 2012)
In a distant future, eighteen-year-old Lugh is kidnapped, and while his twin sister Saba and nine-year-old Emmi are trailing him across bleak Sandsea they are captured, too, and taken to brutal Hopetown, where Saba is forced to be a cage fighter until new friends help plan an escape.
Young Adult.
Young Adult
Keywords: Brothers and sisters -- Juvenile fiction; Hand-to-hand fighting -- Juvenile fiction; Kidnapping -- Juvenile fiction; Orphans -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Fiction; Coming of age -- Fiction; Hand-to-hand fighting -- Fiction; Kidnapping -- Fiction; Orphans -- Fiction; Science fiction; Twins -- Fiction; Bildungsromans; Kidnapping -- Fiction; Martial arts -- Fiction; Orphans -- Fiction; Science fiction; Siblings -- Fiction; Twins -- Fiction; Bildungsromans; Science fiction